(untitled) (Revista de Educação Pública, 2017)
SAMMUT, Gordon; ANDREOULI, Eleni; GASKELL, George; VALSINER, Jaan. The Cambridge Handbook of Social Representations. Cambridge University Press: Cambridge, 2015. 481 p.